2021
DOI: 10.52963/perr_biruni_v10.n3.26
|View full text |Cite
|
Sign up to set email alerts
|

Social Anxiety, Depression, Coping Self-Efficacy, and Coping Strategies Among College Students

Abstract: The transition to college and its associated social challenges could trigger social anxiety and depression among young college students. There is a paucity of literature relating coping self-efficacy, coping strategies, social anxiety and depression. The current study aims to fill this gap by finding the contributions of gender, coping self-efficacy (CSE), and coping strategies onto the levels of social anxiety and depression among college students. It also aims to find race-ethnicity differences, considering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…This indicates that the development of students' depressive symptoms depends on their use of emotion-focused coping strategies. These findings are supported by previous studies that showed coping strategies could predict depressive symptoms ( Dugyala and Poyrazli, 2021 , Faronbi et al, 2021 , Lopes and Nihei, 2021 ). Lopes & Nihei (2021) revealed that various coping strategies, including denial, substance use, behavioral disengagement and self-blame had a positive predictive effect on depressive symptoms in Brazilian students.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This indicates that the development of students' depressive symptoms depends on their use of emotion-focused coping strategies. These findings are supported by previous studies that showed coping strategies could predict depressive symptoms ( Dugyala and Poyrazli, 2021 , Faronbi et al, 2021 , Lopes and Nihei, 2021 ). Lopes & Nihei (2021) revealed that various coping strategies, including denial, substance use, behavioral disengagement and self-blame had a positive predictive effect on depressive symptoms in Brazilian students.…”
Section: Discussionsupporting
confidence: 90%
“… Faronbi et al (2021) noted that coping strategies, including religious coping, humour, behavioural disengagement and use of emotional social support were significantly associated with depressive symptoms among Nigerian nursing students. Dugyala & Poyrazli (2021) stated that coping strategies, including substance use, behavioral disengagement and self-blame significantly predicted depressive symptom among northeastern university students. It might be that using inappropriate coping strategies to deal with stressful circumstances could lead to adverse outcomes for mental health, especially depression ( Freyhofer et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, Kraft et al (2021) reported that cognitive mechanisms underlying depression were also associated with social anxiety among college students. Another study reported that dysfunctional coping strategies, including substance use, were associated with depression and social anxiety symptoms among college students (Dugyala & Poyrazli, 2021). A recent systematic review reported that individuals with social anxiety and alcohol use disorder most commonly reported co-occurring depression symptoms, above that of any other mental health symptoms assessed (Oliveira et al, 2018).…”
Section: Introductionmentioning
confidence: 99%